Cytochrome P450 enzymes mediated by DNA methylation is involved in deoxynivalenol-induced hepatoxicity in piglets - Aimei Liu (Animal Nutrition, 2022)
Deoxynivalenol (DON) is an inevitable contaminant in animal feed and can lead to liver damage, then decreasing appetite and causing growth retardation in piglets. Although many molecular mechanisms are related to hepatoxicity caused by DON, few studies have been done on cytochrome P450 (CYP450) enzymes and DNA methylation. To explore the role of CYP450 enzymes and DNA methylation in DON-induced liver injury, male piglets were fed a control diet, or diet containing 1.0 or 3.0 mg/kg DON for 4 weeks. DON significantly raised the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and glutamyl transpeptidase (GGT) (P < 0.01), leading to liver injury. In vivo study found that DON exposure increased the expression of CYP450 enzymes (such as CYP1A1, CYP2E1, CYP3A29) (P < 0.05), and disturbed the expression of nicotinamide N-methyltransferase (NNMT), galanin-like peptide (GALP) and insulin-like growth factor 1 (IGF-1) (P < 0.05), in which DNA methylation affected the expression of these genes. In vitro study (human normal hepatocytes L02) further proved that DON elevated the expression of CYP1A1, CYP2E1 and CYP3A4 (P < 0.05), and inhibited cell growth in a dose-dependent manner, resulting in cell necrosis. More importantly, knockdown of CYP1A1 or CYP2E1 could alleviate DON-induced growth inhibition by promoting IGF-1 expression. Taken together, increased CYP450 enzymes expression was one of the mechanisms of hepatoxicity and growth inhibition induced by DON, suggesting that the decrease of CYP450 enzymes can antagonize the hepatoxicity in animals, which provides some value for animal feed safety.